Comparison of antimicrobial effect of bark and aerial parts of Prosopis flexuosa var. depressa against Brucella canis (Veterinary Science, 2017)
Canine brucellosis is a zoonotic disease caused by Brucella canis. The treatment with antibiotics combinations is often not fully effective, with relapses. Plant extracts of Prosopis flexuosa var. depressa have demonstrated antimicrobial activity in vitro over Brucella canis. By Sohxlet extraction with solvents of increasing polarity different fractions were obtained which were tested for growth inhibition in agar dilution to assess what fraction resided in the antimicrobial effect. The methanol fraction of the aerial parts of Prosopis flexuosa var. depressa showed antibacterial action up to dilutions of 1/80. Characterization reactions show the presence of tannin, lipids, carbohydrates, steroid nucleus and triterpene alkaloids, saponins, proteins and amino groups
Keywords: Prosopis SPP; Brucella canis; Plan extract